Analisis Faktor-Faktor yang Mempengaruhi Aktivitas Masyarakat dalam Pemanfaatan dan Konservasi Hutan Mangrove di Pesisir Tangkolak, Kabupaten Karawang: Analysis of Factors Influencing Community Activities in the Utilization and Conservation of Mangrove Forests in the Coastal of Tangskolak, Sukakerta Village, Cilamaya Wetan District, Karawang District - Damay Indrianto, Putra; Abadi, Slamet; Sulandjari, Kuswarini (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2023)
Mangrove coastal areas are areas that are vulnerable to changes and pressures originating from nature or as a result of human activities. Tangkolak is a hamlet that has a mangrove forest of 70 hectares. Mangrove forests have economic and social benefits if managed optimally. Therefore it is necessary to know what are the uses and activities of the community in conservation so that ecosystems and natural resources can be utilized optimally. This study has the objectives: To identify community activities in the utilization and conservation of mangrove forests and the influencing factors. The research method used is qualitative and quantitative methods. The research sample used the Slovin method with a total of 61 respondents. Data collection was carried out through direct observation and interviews. Data analysis with scores, categories and multiple linear regression analysis. The results showed that the highest utilization of mangroves was found in fisheries, then firewood, medicines, and consumption materials. The highest conservation activities in conveying/inviting other people, nurseries, planting, maintenance, labor and material assistance. Simultaneously there is a significant influence between the variables of personal characteristics, motivation, and community environment on community activity variables, and partially community environment variables have a significant effect on community activity variables, while personal characteristic variables and motivational variables do not have a significant effect on community activities. Mangrove utilization activities need to be increased by providing training and counseling to the community so that the community understands and is able to maximize utilization and provide economic value. In addition, the community needs to be equipped with knowledge and technology so that processed mangrove products can be widely marketed.